DISASTER PREPAREDNESS TOWARDS COMMUNITIES’ ANXIETY (A LANDSLIDE CASE STUDY IN LAMKLENG VILLAGE, ACEH BESAR) - Miska Rahmah; M. Dirhamsyah; Marty Mawarpury (RADJA PUBLIKA, 2023)
The impacts of landslide are loss of life, people and livestock get injury, infrastructure, agricultural land, housing damage, economic loss, and anxiety experienced. Anxiety will have negative impacts, such as panic and respiratory disorders. This study aimed to analyze the correlation between disaster preparedness and anxiety, the effect of disaster preparedness on anxiety, the level of community disaster preparedness, and the level of community anxiety. This study used a correlational quantitative research design. A questionnaire of Google forms was used as a data collection technique. LIPI-UNESCO/ISDR was a parameter scale for preparedness variables, and HARS (Hamilton Anxiety Rating Scale) for anxiety variables. The total number of respondents was 74, and a random sampling technique and Slovin's formula were used to select the sample for this study. Data sources are secondary data and primary data. Descriptive statistics, univariate analysis, and Pearson product-moment were used for analyzing the data. The disaster preparedness in Lamkleng was in the almost ready category with an index of 63, and the community's anxiety level was 85.1% and in the serious category, and there was a relationship between disaster preparedness and anxiety.